Analysis of Sharia Kalsel Bank Service Quality in Banjarmasin City Using the Importance Performance Analysis Method - Wahab, Abdul; Fitriana, Yunisia; Mahdiya, Ilma (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Purpose: The purpose of this research is to discover how the service satisfaction level of Sharia Kalsel Bank in Banjarmasin City is being improved using the use of importance-performance analysis.Design/Method/Approach: This study is a field study with a quantitative descriptive approach. Purposive sampling is a non-probability sampling technique that involves taking samples based as being a customer of Sharia Kalsel Bank for at least one year, with a sample of 100 respondents.Findings: This study show that the service quality of Sharia Kalsel Bank in Banjarmasin City does not meet the criteria for excellent or best service because there is a gap between the average value of performance level and the average value of interest/importance level. The following service factors are identified as needing to be improved on a priority basis using the Cartesian diagram: 4 (Provide service within the estimated time), 7 (Fast service), 14 (Employees give individual (personal) attention to customers regardless of social status), 15 (Full attention of employees to give service for customer), 16 (Prioritize customers need), and 17 (Employees who understand customer needs), 23 (Contracts used in accordance with Al-Quran Hadith, and DSN Fatwas).Originality/Values: The results of measuring the level of customer service satisfaction and the proposed priority actions that can be taken to improve the quality of service at Bank Kalsel Syariah Banjarmasin City.Â